Implementation of child-friendly school system in the first congressional district of La Union - Orfiano, Connie A. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2022)
This Mixed Methods study identified and analyzed the level of implementation of Child-Friendly School System in the 9 central schools in the First Congressional District of La Union. Data were collected using the survey on Child-Friendly School System. The participants were the nine (9) principals of Central Schools. The data gathered were treated statistically using percentages. For the qualitative part, data were gathered using a semi-structured interview questions administered through one- on -one interview. It was found that the principals had very highly implemented the goals stipulated under the Child-Friendly School System (CFSS). Professional growth and development and operating in the interest of the learners were the best practices in implementing the CFSS. Inadequate resources and limited opportunities to be with the learners were the challenges in sustaining CFSS. Support from community and promotion of the values that CFS and education bring were the coping strategies to address the challenges. It is concluded that the principals realize most of the goals of the CFSS which led to the conducive teaching-learning environment. It was recommended that the thematic model and the validated Three-Year Strategic plan on sustaining Child- Friendly School should be adopted and implemented by the central schools in the First Congressional District of La Union.
References : pages 80-84.
CHED-La Union
Keywords: Education, Elementary -- Aims and objectives